2023
DOI: 10.3389/fnut.2023.1175008
|View full text |Cite
|
Sign up to set email alerts
|

Alleviative effects of pinostrobin against cadmium-induced renal toxicity in rats by reducing oxidative stress, apoptosis, inflammation, and mitochondrial dysfunction

Abstract: IntroductionCadmium (Cd) is a highly toxic heavy metal that can be found everywhere in the environment and can have harmful effects on both human and animal health. Pinostrobin (PSB) is a bioactive natural flavonoid isolated from Boesenbergia rotunda with several pharmacological properties, such as antiinflammatory, anticancer, antioxidant, and antiviral. This investigation was intended to assess the therapeutic potential of PSB against Cd-induced kidney damage in rats.MethodsIn total, 48 Sprague Dawley rats w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 87 publications
0
11
0
Order By: Relevance
“…Accordingly, numerous researchers have shown the antiradical potentials of PN in previously published reports. 33 , 60 , 61 Moreover, Ijaz et al 29 reported significant radical quenching activity of PN in cadmium-mediated oxidative stress in rats represented by an upsurge in the CAT, GSR, SOD and GSH-PX and down-modulation of MDA levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, numerous researchers have shown the antiradical potentials of PN in previously published reports. 33 , 60 , 61 Moreover, Ijaz et al 29 reported significant radical quenching activity of PN in cadmium-mediated oxidative stress in rats represented by an upsurge in the CAT, GSR, SOD and GSH-PX and down-modulation of MDA levels.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, numerous researchers have shown the antiradical potentials of PN in previously published reports. 33,60,61 Moreover, Ijaz et al 29 reported significant radical quenching activity of PN in cadmium-mediated oxidative stress in rats represented by an upsurge in the CAT, GSR, SOD and GSH-PX and downmodulation of MDA levels. TNF-α is a well-documented pro-inflammatory cytokine that is released from monocytes and macrophages and is commonly secreted during the early stages of acute and chronic inflammatory diseases (colon cancer).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…COX-2 is an enzyme mediating the progression of inflammation ( Babar et al, 2024 ). Cd exposure mediated renal damage with considerably enhanced inflammatory indices, including IL-1β, TNF-α and IL-6, inducible COX-2 activity in rats ( Ijaz et al, 2023 ). So, our research results showed that Cd treatment markedly aggravated renal inflammatory damage evidenced by an increase in the IL-8, TNF-α, COX2 and IL-6 contents and protein expression levels in the chicken kidney.…”
Section: Discussionmentioning
confidence: 99%
“…The first favours atmospheric recycling, while the second lead to bioaccumulation in sediments and aquatic species. This bioaccumulation process leads to cumulative effects on the occurrence of biomagnification through the food chain [ 14 ] . Sea organisms accumulate these contaminants primarily by uptake through the skin and gills via surface contacts with sediments, industrial effluent, wastewater, as well as via the food they consume [ 15 ] .…”
Section: Introductionmentioning
confidence: 99%